The pyriproxyfen metabolite, 4′–OH–PPF, disrupts thyroid hormone signaling in neural stem cells, modifying neurodevelopmental genes affected by ZIKA virus infection. (15th September 2021) - Vancamp, Pieter; Spirhanzlova, Petra; Sébillot, Anthony; Butruille, Lucile; Gothié, Jean-David; Le Mével, Sébastien; Leemans, Michelle; Wejaphikul, Karn; Meima, Marcel; Mughal, Bilal B.; Roques, Pierre; Remaud, Sylvie; et al.
Abstract: North-Eastern Brazil saw intensive application of the insecticide pyriproxyfen (PPF) during the microcephaly outbreak caused by the Zika virus (ZIKV). ZIKV requires the neural RNA-binding protein Musashi-1 to replicate. Thyroid hormone (TH) represses MSI1 . PPF is a suspected TH disruptor. We hypothesized that co-exposure to the main metabolite of PPF, 4′–OH–PPF, could exacerbate ZIKV effects through increased MSI1 expression. Exposing an in vivo reporter model, Xenopus laevis, to 4′–OH–PPF decreased TH signaling and increased msi1 mRNA and protein, confirming TH-antagonistic properties. Next, we investigated the metabolite's effects on mouse subventricular zone-derived neural stem cells (NSCs). Exposure to 4′–OH–PPF dose-dependently reduced neuroprogenitor proliferation and dysregulated genes implicated in neurogliogenesis. The highest dose induced Msi1 mRNA and protein, increasing cell apoptosis and the ratio of neurons to glial cells. Given these effects of the metabolite alone, we considered if combined infection with ZIKV worsened neurogenic events. Only at the fourth and last day of incubation did co-exposure of 4′–OH–PPF and ZIKV decrease viral replication, but viral RNA copies stayed within the same order of magnitude. Intracellular RNA content of NSCs was decreased in the combined presence of 4′–OH–PPF and ZIKV, suggesting a synergistic block of transcriptional machinery . Seven out of 12 tested key genes in TH signaling and neuroglial commitment were dysregulated by co-exposure, of which four were unaltered when exposed to 4′–OH–PPF alone. We conclude that 4′–OH–PPF is an active TH-antagonist, altering NSC processes known to underlie correct cortical development. A combination of the TH-disrupting metabolite and ZIKV could aggravate the microcephaly phenotype. Graphical abstract: Image 1 Highlights: The pyriproxyfen metabolite, 4′–OH–PPF, antagonizes thyroid hormone action. 4′–OH–PPF reduces neural stem cell proliferation and increases apoptosis in vitro . 4′–OH–PPF alters neural stem cell fate, increasing the neuro/glia ratio. 4′–OH–PPF increases Musaschi-1, a protein the ZIKA virus needs to replicate. 4′–OH–PPF exposure alters ZIKA virus effects on gene expression.